Intermediate Algebra for College Students (7th Edition)

Published by Pearson
ISBN 10: 0-13417-894-7
ISBN 13: 978-0-13417-894-3

Chapter 7 - Section 7.5 - Multiplying with More Than One Term and Rationalizing Denominators - Exercise Set: 31

Answer

$6$

Work Step by Step

RECALL: $(a+b)(a-b)=a^2-b^2$ Use the formula above with $a=3\sqrt2$ and $b=2\sqrt{3}$ to obtain: $=(3\sqrt{2})^2- (2\sqrt{3})^2 \\=3^2(2) -2^2(3) \\=9(2)-4(3) \\=18-12 \\=6$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.